Artificial Intelligence, Post-Work and Music Labor - Srđan Atanasovski (INSAM)
The recent – purportedly rapid – development of AI tools has again resurrected the actuality of post-work u-/dystopias. Drawing on discursive topoi which have become popular since the post-WW2 automatization surge, AI post-work now advances into the field of white-collar labor, but also creative, artistic, and even music labor. In this paper I aim to analyze the emergent arrival of the post-work thesis into music labor. I will draw on prominent critics of automatization, AI and post-work discourses, such as Pierre Naville, Aaron Benanav and Jason Resnikoff, to show that these discourses are not only unsubstantiated, but are instrumentalized in order to depreciate the value of concrete labor in music production.